PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE HUMANISTIS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS 8C DI SMP AHMAD YANI KOTA BATU - Yusfia Arifatul Azizah; Ach. Faisol; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Education is the process of each individual making choices regarding the direction of the road to achieve his life goals. Of course this is every god's creature in the world, especially humans and their civilizations have different life goals. It is in these different goals that there must be special expertise in the fields of science, pedagogy or education, and teaching to students who in our country are referred to as